MRI Findings of Patients Presenting with Vertigo to the Otorhinolaryngology OPD of a Tertiary Care Center of Western Nepal - Rai, Shiwani; Koirala, Krishna Prasad; Yogi, Nikunja; Karmacharya, Balgopal; Bhattarai, Aabishkar; Karki, Bijaya (Eastern Green Neurosurgery, 2020)
Background: Dizziness is a common symptom affecting about 30% of people over the age of 65years. In this study, we tried to determine the usefulness of MRI in evaluating the causes of vertigo presenting in ENT outpatient clinics. Materials and methods: We retrospectively analyzed 98 vertigo patients, who came or were referred to outpatient clinics of Otorhinolaryngology Department of Manipal College of Medical Sciences, Pokhara, Nepal. MR imaging of the head and cervical spine was performed in all patients with exception of those with vertigo secondary to trauma, drugs, cardiovascular, or patients in whom MRI was contraindicated. Demographics, comorbidities, and MRI findings were evaluated. Results: There were 98 patients fulfilling the study criteria in our study. There were 41 males (41.84%) and 57 females (58.26%) with M: F ratio of 0.70. The mean age of the patients included in the study was 52.16±14.524 years (21-84 years). Systemic arterial hypertension was the only parameter showing statistically significant against normal and abnormal MRI findings (p-value =0.017) in patients presenting with vertigo. Cervical findings (Prolapsed Disc and Canal stenosis) were the commonest positive findings in MRI (n=27, 27.6%) followed by White matter lesions in the brain (18, 18.4%) and cerebral infarcts (n=12, 12.2%). Conclusion: The utility of MRI may not be high in patients with acutely isolated vertigo however MRI has indicated if it suggests central cause with neurological signs and symptoms, risk factors of the cerebral vascular accident, treatment-resistant cases or cases with diagnostic uncertainty. Abnormalities in MRI are common in patients with co-existing dizziness and systemic arterial hypertension.